Konsep Pemberdayaan Zakat dan Relevansinya terhadap Program Pengentasan Kemiskinan (Studi Pemberdayaan Zakat WIZ Kolaka) - Muhammad Taufan Djafri; Ihwan Wahid Minu; Ade Syamna Maryam (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
Poverty is a social problem that requires serious handling. Zakat is an effective instrument for overcoming poverty from an Islamic perspective. This study aims to analyze the zakat empowerment mechanism of Wahdah Inspirasi Zakat (WIZ) Kolaka City and the effectiveness of its zakat empowerment programs in alleviating poverty. The research method uses a qualitative approach through in-depth interviews with related parties. The results showed that the zakat management mechanism of WIZ Kolaka was quite good, although there were still certain procedures and constraints. WIZ Kolaka's zakat empowerment programs seem significantly helpful in reducing the number of poor people through distributive and productive zakat distribution. Continuous evaluation is needed so that WIZ Kolaka can achieve its goals to the maximum extent. The implication of this research is to provide input for developing policies to alleviate poverty by utilizing zakat.